\(A=x^2+2xy+y^2-4x-4y+1\)
\(A=\left(x+y\right)^2-4\left(x+y\right)+1\)
\(A=3^2-4.3+1\)
\(A=-2\)
\(x^2+2xy+y^2-4x-4y+\)\(1\)
\(=\left(x^2+2xy+y^2\right)-\left(4x+4y\right)+1\)
\(=\left(x+y\right)^2-4\left(x+y\right)+1\)
Thay x+y = 1, ta có:
\(=3^2-4.3+1=-2\)
Bạn tham khảo cách 2 nhé !
\(x^2+2xy+y^2-4x-4y+1\)
\(=\left(x^2+y^2+1+2xy-2x-2y\right)-2x-2y\)
\(=\left[1-\left(x+y\right)\right]^2-2\left(x+y\right)\)
Thay x+y=1 ta có
\(=\left(1-3\right)^2-2.3\)
\(=-2\)
A = x2 + 2xy + y2 - 4x - 4y + 1
A = ( x2 + 2xy + y2 ) - ( 4x + 4y ) + 1
A = ( x + y )2 - 4 . ( x + y ) + 1
Thay x + y = 3 vào A, ta được :
A = 32 - 4 . 3 + 1 = - 2
Vậy : A = - 2